Pengaruh Media Pop-Up Book Digital “Sang Garuda” Pada Pembelajaran Pendidikan Pancasila Terhadap Motivasi Belajar Siswa - khoir, nafi; Ardita Juliyanti; Ika Dian Rahmawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The era of globalization and advances in digital technology has brought considerable challenges to the world of education, one of which is the declining learning motivation among students in Pancasila Education subject, largely attributed to teaching approaches that tend to be repetitive and lack variation. This study aims to examine the effect of implementing the "Sang Garuda" Digital Pop-Up Book media on the learning motivation of third-grade students at SDN Gili Timur 1 in Pancasila Education subject. A quantitative approach with a Pre-Experimental One Group Pre-Test Post-Test Design was employed, involving 22 students selected through saturated sampling technique. Data were gathered using a Likert scale-based questionnaire administered both prior to and following the intervention. The Shapiro-Wilk test revealed that the data did not follow a normal distribution; therefore, hypothesis testing was carried out using the Wilcoxon Signed Rank Test. The results yielded a Z value of -3.321 with Asymp. Sig. (2-tailed) = 0.001 < 0.05, confirming a significant influence of the media on students' learning motivation. The mean score rose from 13.50 to 16.00, with 81.8% of students demonstrating positive improvement. These findings suggest the importance of incorporating nationally-themed digital media as an innovative alternative in Pancasila Education learning to foster greater enthusiasm and active student engagement amid the ever-growing tide of globalization.